Analisis Kesulitan Belajar Matematika Siswa Kelas II Sekolah Dasar pada Materi Waktu - Dea My Fitri (Universitas Muhammadiyah Enrekang, 2023)
Mathematics learning is widely seen as a difficult subject to learn. Due to the need for efforts that must be made to understand the material. Especially at the elementary school level, where this level is the main milestone in the next learning process. One of them is grade II elementary school students in learning math on time material. This study aims to analyze the difficulties experienced by students during the mathematics learning process in mathematics on the material of time. The research used is qualitative research with descriptive methods. In the process of collecting data using a questionnaire with a Likert scale. The study population was grade II elementary school students and the sample was grade II B students from the results of the indicators set by the researcher. The average of each indicator is 63%, this means that the learning difficulties experienced by students are in the high category. The questionnaire is made by categorizing several indicators, namely motivation and interest in learning mathematics, difficulties in understanding and the methods used by the teacher.